Does Community-based Forestry Management Approach Improve the Livelihoods of Local People? A case of Sal-forest area in Bangladesh - Farouque, Mohammad Golam; Fuyuki, Katsuhito; Takashino, Nina (Advances in Social Sciences Research Journal, 2017)
Community-based forest management (CBFM) approach has been implementing in the degraded Sal forest areas since 1989 with an aim to eliminate the main causes of forest depletion as well as alleviate poverty through participation of local people who depend on forest for their livelihoods in Bangladesh. The objective of the study was to explore the impact of CBFM initiative on the livelihoods of local people based on empirical data collected from the CBFM project sites. The study was conducted in two forest ranges of Sakhipur Sal forest area under Tangail district of Bangladesh. The findings indicate that though CFFM initiatives improved the financial capital of respondents to an extent, other livelihood capitals faced constraints and difficulties. Biasness of the CBFM project personnel and social discrimination, inequality issues and social capital differences were emerged between ethnic and non ethic respondents.. Lack of concrete commitment by the CBFM project personnel in particular and forest department in general, CBFM could not fulfill the demands of local people and limited success had been created to improve the overall livelihoods situation. It was reported during field observation that CBFM approach alone was not sufficient to manage and conserve the Sal forests or ensures local people’s basic needs and demands. Therefore, to address the diversified needs of forest dependent local people and to manage and conserve Sal forest in a more sustainable way, the forest department of Bangladesh might initiate a long-term-integrated approach with skilled local forest staff.